Preferences for public long-term care insurance among middle-aged and elderly residents: A discrete choice experiment in Hubei Province, China - Ma, He; Jia, Erping; Ma, Huimin; Pan, Yanzhi; Jiang, Shan; Xiong, Juyang (Frontiers in Public Health, 2023)
Objective: It is critical to incorporate residents’ preferences into the design of long-term care insurance (LTCI). However, little is known about middle-aged and elderly residents’ preferences for personalized need-related attributes of LTCI in China. Through a discrete choice experiment (DCE), we aimed to focus on the direct beneficiaries of LTCI and then elicit their preferences for LTCI under a hypothetical scenario of dysfunction. Methods: Attributes and levels were defined through a literature review and two rounds of expert consultations (n=8). A D-optimal fractional factorial design was used to generate the DCE questionnaire. Face-to-face interviews with middle-aged and elderly residents were conducted in two cities in Hubei Province, China, between November and December 2020. A mixed logit model was utilized for estimation. Results: Five attributes were identified and incorporated into the DCE questionnaire. A total of 390 participants completed DCE questionnaires. Care facilities, care content, reimbursement rate, caregivers, and annual premium per person all had a significant impact on residents’ preferences. Residents had significantly higher preferences for the LTCI scheme with home and community-based care centers (β=1.40, p < 0.01), multi-level services (β=0.44, p < 0.01), 90% reimbursement rate (β=0.37, p < 0.01), and sufficiently trained caregivers (β=0.26, p < 0.01). Individual characteristics, such as gender, employment, and education level were the factors that drove heterogeneity in preferences for LTCI. Conclusion: The care facility was the most preferred LTCI attribute among middle-aged and elderly residents, followed by care content, reimbursement rate, caregivers, and annual premium per person. The design of the LTCI scheme in China needs to take these findings into account to maximize the utility for direct beneficiaries of LTCI and enhance their enrollment.